Biographicity as a project. On the foundation of a research programme on lifelong learning - Alheit, Peter (Adult Education Discourses, 2025)
The following considerations are a cautious attempt to answer the question how modern biographies can be understood and which impact their real course has on social learning processes. Four conceptual accesses discuss possible solutions: a “time – diagnostic access” (section 1), a “phenomenological access” (section 2), a “comparative access” (section 3) and an “alternative theoretical access” (section 4). The first thought relates to the observation that late modern life courses seem – unplanned – to be becoming a kind of “laboratory” in which we have to develop skills that have no “curriculum” for the time being. The second step will be to clarify the phenomenological originality of the concept “biography”. Does this concept really announce a new problem or is it just another label for questions that have long been known? The specific pedagogical applicability of the term will then be discussed. The large number of biography – oriented approaches, particularly in the educational sciences, is certainly not an indication of their indispensability, but it is also not necessarily the symptom of a mere fashion. Finally, in a pointed discussion of a polemic remark by Pierre Bourdieu, the outline of a programmatic framework concept will be presented.